1999
DOI: 10.1097/00007691-199904000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 6-Thioguanine and 6-Methylmercaptopurine Metabolites in Renal Transplantation Recipients and Patients With Glomerulonephritis Treated With Azathioprine

Abstract: The metabolism of azathioprine (AZA) was studied by monitoring the concentrations of red blood cell (RBC) 6-thioguanine nucleotides (6-TGN) and of 6-methylmercaptopurine metabolites (6-mMP) in 27 renal transplantation recipients and in 10 patient subjects with glomerulonephritis (GN). Concentrations of 6-TGNs and 6-mMP metabolites were measured using high-performance liquid chromatography (HPLC). Six patients from the group of renal transplantation recipients were also administered allopurinol. Median values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
0
14
0
8
Order By: Relevance
“…Hepatotoxicity following AZA dose escalation has been shown to occur in about one in four patients treated with AZA and frequently leads to the withdrawal of therapy 41 . Concomitant allopurinol therapy with reduced dose of AZA improves clinical response by increasing 6TGNs and by‐passes AZA‐induced hepatoxicity 21, 22, 24 . Our results demonstrated that allopurinol co‐therapy with AZA reduced 6TU excretion below detection levels.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Hepatotoxicity following AZA dose escalation has been shown to occur in about one in four patients treated with AZA and frequently leads to the withdrawal of therapy 41 . Concomitant allopurinol therapy with reduced dose of AZA improves clinical response by increasing 6TGNs and by‐passes AZA‐induced hepatoxicity 21, 22, 24 . Our results demonstrated that allopurinol co‐therapy with AZA reduced 6TU excretion below detection levels.…”
Section: Discussionmentioning
confidence: 57%
“…Prescription of normal doses of AZA for a patient receiving allopurinol can lead to severe myelotoxicity 20 . However, allopurinol has been deliberately combined with low‐dose AZA in an attempt to improve AZA efficacy 21–24 …”
Section: Introductionmentioning
confidence: 99%
“…A therapeutic benefit for a combination of low-dose allopurinol and thiopurines was first demonstrated in renal transplantation, where the addition of allopurinol improved graft survival 44 and also increased 6TGN levels. 45 In 2005, the efficacy of combination therapy was first demonstrated in a group of 15 patients with clinically active IBD, who were documented thiopurine shunters (mean 6TGN = 186, mean 6MMP = 10 380). With the addition of 100 mg allopurinol and a dose reduction of AZA to 25-50% of the original thiopurine dose, this adverse metabolic profile was reversed with mean 6TGN increasing to 385 and mean 6MMP decreasing to 1732 (P < 0.001).…”
Section: The Role Of Allopurinol In Thiopurine Shuntersmentioning
confidence: 99%
“…This strategy was therefore abandoned and allopurinol instead found its niche in the treatment of gout [1]. In 1993 it was reported that coprescription of AZA and allopurinol improved renal graft survival and optimized thiopurine metabolite profiles [102,103]. More recently interest in combination treatment using low-dose AZA/MP and allopurinol in IBD has focused on bypassing thiopurine hyper methylation.…”
Section: Nongenetic Factors Affecting Thiopurine Metabolismmentioning
confidence: 99%